Unpacking the Renewable Pull Effect: Conditions for Green Industrial Relocation - Sven Colen; Alwine Mohnen (Business Strategy and the Environment, 2025)
The renewable pull effect theoretically leads to the relocation of green production facilities within energy-intensive industries to regions rich in renewable energy resources. This study employs a qualitative research design, integrating the analytic hierarchy process method, by interviewing top managers and experts from globally leading steel and chemical corporations, predominantly based in Europe and Germany. The findings reveal that whereas factors associated with the renewable pull effect are most influential in green production location decisions, three critical conditions must be met for this effect to translate into actual green relocations: weaker agglomeration and demand pull effect, limited counteracting subsidies from regulatory bodies, and fulfillment of essential socio-political and environmental prerequisites. This study demonstrates that the renewable pull effect only conditionally drives green relocations, providing the first comprehensive evaluation of the key factors shaping green relocations within the ongoing academic debate. Moreover, by providing empirical insights from leading industry practitioners, the study advances the existing literature, which has been predominantly based on theoretical models and techno-economic analyses. Additionally, the study suggests several foremost avenues for future research. Finally, it delivers practical implications for energy-intensive industries' top management and policymakers in both renewable-energy-rich and scarce regions, informing strategic decision-making for sustainable transition.
Keywords: 650; analytical hierarchy process; direct-reduced iron; energy-intensive industries; green ammonia; green relocation; industrial relocation; renewable pull effect; sustainable transition